Utilização de drones como suporte à gestão de segurança e infraestrutura na Universidade Federal de Goiás - Silva, Ubirajara Pereira (2024)
In recent decades, the application of emerging technologies has revolutionized security and infrastructure management in educational institutions, promoting greater efficiency in public spending and faster response for users: students, educational technicians, teachers, and the academic community. This research aimed to evaluate some remote sensing techniques based on unmanned aerial vehicles (drones) equipped with RGB and thermal sensors to support the safety and physical maintenance protocols of the Federal University of Goiás. Thus, applications in internal surveillance, especially in areas covered by vegetation, as well as in building infrastructure, were considered, in this case focusing on infiltration and water accumulation on roofs, which could enhance the proliferation of arboviruses related to the Aedes aegypti mosquito, transmitter of dengue, chikungunya, zika, and yellow fever. The study was conducted at the Samambaia Campus in Goiânia between the years 2022 and 2024, involving drone flights over dense and sparse vegetation areas (to locate people within these environments), and over selected campus buildings to detect gutter obstructions, water accumulations, and roof damages. We found good potential of the drones in detecting thermal anomalies in sparse forests (indicating the presence of humans), examining damages, and visualizing the conservation state of the University's buildings. The research allowed us to verify the versatility of the technologies employed in monitoring structural conditions, focusing on building roofs, and the security aspect of the Samambaia campus, offering an aerial perspective, notably more efficient than ground inspections. It is concluded that the University administration should be equipped with drones embedded with RGB and thermal imaging sensors, with significant gains in security and infrastructure management.